Internal kinematics of Globular Clusters: Current state of the art, issues, and what to expect from the future. Issue Volume 14:Issue S351(2019) (May 2019) - Bellini, Andrea
Abstract: The advent of the Gaia mission is bringing astrometry to a new renaissance. Although Gaia will make important breakthroughs in many different scientific areas, stars in the crowded central fields of globular clusters (GCs) and at the faint end of the color-magnitude diagram are and will be out of Gaia 's reach. The Hubble Space Telescope ( HST ) is an excellent astrometric tool that has allowed us to distinguish and measure positions and brightness of faint stars in pencil-beam fields down to the very center of some GCs. Gaia and HST are two wonderful, complementary tools, but are yet far from being able to offer a complete dynamical picture of GCs. There is now great prefiguration for what the next-generation telescopes will be able to do, both ground- and space-based. This document highlights strengths and weaknesses of different facilities at different spatial and spectral regimes.